Decision Support Systems (DSS): A survey - H. W. Ittmann (South African Journal of Business Management, 1984)
Interest in aiding and supporting decision-making through the use of computers has been stimulated by technological developments in areas such as personal computers, computer networks, large data bases, colour graphics and computer-based models. These uses are known as Decision Support Systems (DSS) and imply computer systems designed to extend managers' capabilities, and at the same time to integrate these uses into existing managerial activities and needs. During the past few years there have been rapid international developments in the DSS field. In South Africa this trend is also noticeable, although on a smaller scale. The object of this article is to give a survey of Decision Support Systems by defining the concept and by showing how it relates to other fields, and to present a framework of the typical functions and components of such a system. Some practical applications are discussed for illustrative purposes.
Keywords: 650